The Evaluation of Nickel Toxicty on Lamellidens marginalis - S. P. Zambare, A.V. Andhale, H. M. Pawar; S. P. (Recent Research in Science and Technology, 2011)
The study deals with calculation of LC10 and LC50 values for 24 and 96 hours. In present study, the toxicity of Nickel Chloride on Lamellidens marginalis showed that with increasing time and concentration, mortality rate increase.Ã‚Â From this investigation, the exact cause of their death is not known but it is proved that nickel chloride brings some changes in physiochemical properties of water and it affects the metabolic rate severally leading to the death of animals. The toxicity study provides the level of safe concentration of toxicant.